Climate change promotes transitions to tall evergreen vegetation in tropical Asia. (13th July 2020) - Scheiter, Simon; Kumar, Dushyant; Corlett, Richard T.; Gaillard, Camille; Langan, Liam; Lapuz, Ralph Sedricke; Martens, Carola; Pfeiffer, Mirjam; Tomlinson, Kyle W.
Abstract: Vegetation in tropical Asia is highly diverse due to large environmental gradients and heterogeneity of landscapes. This biodiversity is threatened by intense land use and climate change. However, despite the rich biodiversity and the dense human population, tropical Asia is often underrepresented in global biodiversity assessments. Understanding how climate change influences the remaining areas of natural vegetation is therefore highly important for conservation planning. Here, we used the adaptive Dynamic Global Vegetation Model version 2 (aDGVM2) to simulate impacts of climate change and elevated CO2 on vegetation formations in tropical Asia for an ensemble of climate change scenarios. We used climate forcing from five different climate models for representative concentration pathways RCP4.5 and RCP8.5. We found that vegetation in tropical Asia will remain a carbon sink until 2099, and that vegetation biomass increases of up to 28% by 2099 are associated with transitions from small to tall woody vegetation and from deciduous to evergreen vegetation. Patterns of phenology were less responsive to climate change and elevated CO2 than biomes and biomass, indicating that the selection of variables and methods used to detect vegetation changes is crucial. Model simulations revealed substantial variation within the ensemble, both in biomass increases and in distributions of different biome types. Our results have important implications for management policy, because they suggest that large ensembles of climate models and scenarios are required to assess a wide range of potential future trajectories of vegetation change and to develop robust management plans. Furthermore, our results highlight open ecosystems with low tree cover as most threatened by climate change, indicating potential conflicts of interest between biodiversity conservation in open ecosystems and active afforestation to enhance carbon sequestration. Abstract : Tropical Asia includes a rich biodiversity, threatened by climate change and intense land‐use. We used a dynamic vegetation model to investigate how an ensemble of climate change scenarios may influence future biomass, vegetation height, and phenology in tropical Asia. We found a robust trend of increasing vegetation biomass, and transitions to taller, evergreen vegetation. Open ecosystems with deciduous vegetation such as grasslands and savannas were most susceptible to climate change. Understanding climate change impacts on remaining areas of natural vegetation is essential for conservation planning and management in tropical Asia.